Village Information System Design with Mobile Development Life Cycle Approach - Murtia, Sri; Saputra, Riki; Ramadani, Niska (Universitas Putra Indonesia YPTK Padang, 2025)
Mobile technology can provide great opportunities for village governments to improve public services and make village governance more transparent. Lolo Kecil Village still faces several problems in services, such as manual and time-consuming administrative processes, low public access to village information and activities, and low citizen participation in the decision-making process. This hampers service performance and makes the community less trusting of the village government. This study aims to design a mobile-based village information system using the Mobile Development Life Cycle (MDLC) approach. The MDLC approach is structured through the stages of planning, needs analysis, system design, and mobile application development. This system is intended to facilitate village administration processes such as delivering letters and other public services online, as well as increasing transparency through access to village information and activities. Through the complaint feature and discussion forum, the village information system can help the community communicate with the village government and provide direct input to village officials. The results of the system design implementation show that MDLC works well to create a stable, responsive, and easy-to-use mobile application. As a result, this application can function as a strategic tool to accelerate the digital transformation of villages, increase the accountability of village governments, and strengthen the relationship between village officials and the community through more open and clear communication. As a result, the level of public satisfaction with the services provided by the village government increased.